(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Adhesions means fibrous or scar tissue that results from the healing process. Up to 95% of patients who have surgery develop adhesions. Adhesions formation and its long term sequel is a well known complication of the surgery but unfortunately very little is investigated about the prevention. The long term morbidities such as chronic pelvic pain, secondary infertility, hospital readmission, bowel obstruction, difficult repeat C/S with increased bleeding, longer operative time, injury to bowel ,bladder, ureters and placental accreta spectrum disorder from adhesions are the main concern. The cost for these adhesions is extreme burden for the developing countries. Several preventive agents against postoperative adhesions have been investigated. The proper surgical technique remains the cornerstone for good outcomes and risks reduction. Careful tissue handling, keeping tissue moist, meticulous homeostasis, minimization of tissue ishcaemia and avoiding excessive tissue desiccation, the use of micro and a traumatic instruments are very important to prevent the adhesive disorders. Several chemical agents, mechanical barriers and hydrofloatation are being used which seems to be promising. But all of them have some limitations. All these Barriers are being used widely but need to be properly evaluated, before its routine use. FDA approved Barrier Seprafilm, Hydrofloation Adept are popular but also CoSeal, SurgiWrap and Plasmax( not FDA approved ) are getting much popularity. Oxidized regenerated cellulose is promising but for C/S is not properly evaluated. The chemical barriers like NSAID, Steroids, antifibrinolytic agents and anticoagulant are being used since ancient period but they are not proved to be superior to adhesive barriers. In the current state of knowledge, none can replace the good surgical technique. Therefore along with the training of appropriate surgical technique, preclinical or clinical studies are still necessary to evaluate the effectiveness of the several proposed prevention strategies and more researches are time demanding to prevent postoperative adhesions. J Bangladesh Coll Phys Surg 2017; 35(2): 86-90